2023
DOI: 10.3390/ma16041722
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sustained Loading on the Direct Shear Behaviour of Recycled C&D Material–Geosynthetic Interfaces

Abstract: Recycled construction and demolition (C&D) wastes have been pointed out as a feasible alternative to traditional backfill materials of geosynthetic-reinforced structures, but the current knowledge about the interface behaviour between these unconventional (recycled) materials and the reinforcement is still limited, particularly as far as the time-dependent response is concerned. In this study, a series of large-scale direct shear tests was conducted using an innovative multistage method to evaluate the inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…Then, all the components required to describe the hydration processes were chosen, including H, C, N, O, Na, Mg, Al, Si, S, Cl, K, Ca, and Fe. The activity and ionic strength of the ions, such as Ca 2+ , were calculated using the Extended Debye-Hückel model in Equation (2). Afterwards, the mix proportions for the pastes (Table 2) were next input into GEMS and the reactions were performed.…”
Section: Thermodynamic Model Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, all the components required to describe the hydration processes were chosen, including H, C, N, O, Na, Mg, Al, Si, S, Cl, K, Ca, and Fe. The activity and ionic strength of the ions, such as Ca 2+ , were calculated using the Extended Debye-Hückel model in Equation (2). Afterwards, the mix proportions for the pastes (Table 2) were next input into GEMS and the reactions were performed.…”
Section: Thermodynamic Model Simulationmentioning
confidence: 99%
“…Low carbon cementitious materials (LCMs) are becoming more and more popular in mine backfills [1,2], bridges [3], dams [4], and buildings [5] due to their low cement and high solid waste content, which makes the materials more affordable and have a lower CO 2 footprint. This is due to the significant environmental impact associated with coal mining and cement manufacturing.…”
Section: Introductionmentioning
confidence: 99%
“…Designers must also consider essential parameters for a safe and economical design, strengthening its position as a desirable alternative [13]. In the past decades, in addition to the research evaluating the environmental and economic aspects related to using RCDW materials [20][21][22][23][24][25], several studies have reported the potential substitution of natural aggregates by RCDW materials in pavement layers [6,[26][27][28][29][30][31][32][33] and backfill material for geosynthetic reinforced structures [8,12,[34][35][36][37][38][39][40][41][42]. However, Delongui et al [26] emphasized that the RCDW characteristics are valid for the research's specific application conditions (e.g., type of CDW generated, recycling process).…”
Section: Introductionmentioning
confidence: 99%